A assembleia de classe como recurso didático para a construção da argumentação moral na educação básica - Oliveira, Cristiane Santiago de (Universidade Federal de São Carlos, 2021)
This study arises from reflections on the educational phenomenon experienced in pedagogical practices about the difficulties that students have to debate, discuss and expose their opinions through arguments, since this competence is mandatory content of mother tongue classes, especially in the years end of Elementary School II (9th years) and High School. Therefore, this research studied, discussed and analyzed the effectiveness of the class assembly as a didactic resource in the teaching and learning processes, in the initial grades of Elementary School II (6th and 7th years). We are based on the Theory of Communicative Action from the perspective of Habermas' moral argument (2003, 2012) and on Paulo Freire's dialogic and emancipatory education (1967, 1996, 2013, 2019, 2020a,b,c). We used the qualitative approach in proposing four class assemblies with students between ten (10) and twelve (12) years old, having as mediator the researcher who also teaches classes in this class. The results showed that the assemblies are a powerful didactic resource for working with moral argumentation, as long as the mediation and the pedagogical intentionality proposed by the educator has as a specific objective the dialogical and argumentative resourcefulness in the community, in our case, the group of students. The contextualization and the collective decision to discuss a certain content, which has meaning and sense for the collectivity, is another strong assumption to reach the educational objectives with the emphasis on the argumentation that it becomes and to have a power of influence more connected with the reality and the educational process experienced and experienced in the assembly.
The class assembly as a didactic resource for the construction of moral argumentation in basic education
Keywords: Argumentação moral; Assembleia de classe; Dialogismo; Autonomia; Mediação; Moral argumentation; Class assembly; Dialogism; Autonomy; Mediation; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM